Pandan (Pandanaceae) in Flores Island, East Nusa Tenggara, Indonesia: an economic-botanical study - Susiarti, Siti; Djarwaningsih, Tutie; Keim, Ary Prihardhyanto (REINWARDTIA, 2013)
The people in the Indonesian province of Nusa Tenggara Timur (then East Lesser Sunda Islands) consist of manyÂ  ethnicÂ  groups,Â  eachÂ  withÂ  theirÂ  ownÂ  local languages. The island of Flores is the second largest island within the East Lesser Sunda Islands. The island is inhabited by 10 ethnic groups, in which four are regarded as the dominant groups:Â  Flores, Ende, Lio and Manggarai. The pandan flora of the island is still largely unknown; the same is for their ethnobotany. The aim of this current study is to know the traditional usages and potential uses of pandan flora in the Flores Island. The study was carried out in three regencies:Â  Ende, Nagekeo and Manggarai. The result of this study shows that there are four species of Pandanus (P. amaryllifolius, P. dubius, P. kaernbachii, and P. tectorius) and one species of Freycinetia (F. insignis) are recorded from the areas understudy.Â  The presence of P. kaernbachii in Flores Island is a new record.Â  The people also recognises the diversity of Pandanaceae, especially from the genus Pandanus, in which they are known by local names such as âpandaâ, âreâaâ, âwakuâ, and âmbojoâ.Â  Main usages of Pandanus are as material sources for handicrafts (mats, coffee bowls, and hats), dye, flavourings, funeral offering, and ornamental plant.